El glosario escondido en El arte culinario (1900) de Adolfo Solichón. - CARPI, ELENA; DE BENI, MATTEO (Scripta)
This article analyses the «Vocabulario de varios términos culinarios» included in El arte culinario (Madrid, Romo y Füssel, 1900), written by the chef and gourmet Adolfo Solichón, «disciple of Casa Lhardy». After exploring the historical context and describing some author's biographical data, some aspects related to the gastronomy of the late nineteenth century and also the main paratextual features of the glossary, the lexicon of Solichon's «hidden vocabulary» is analysed considering its macrostructure. More specifically, the analysis focuses on the inclusion of neologisms, compounds, and Gallicisms.